Implementasi Projek Penguatan Profil Pelajar Pancasila Rahmatan Lil Alamin Dalam Konteks Kurikulum Merdeka - Maulidah, Evi; Siti Hamidahtur Rofi’ah; Wildania Unsika (STAI AL-AMIN, 2025)
Using a qualitative descriptive approach through observation, interviews, and documentation, this study investigates the Pancasila Rahmatan Lil Alamin Student Profile Strengthening Project (P5RA) implementation at MI Ar Raudlah Sukorambi Jember in the context of the Independent Curriculum and its relevance to the P5RA. The findings show that the P5RA guidelines must be followed when implementing P5RA. Students, staff, and facilities presented obstacles for MI Ar Raudlah, but they were overcome to the best of the school's ability. In addition to offering a P5RA implementation strategy that other schools might use, this study adds to the body of knowledge on character education.